Electroacupuncture versus sham electroacupuncture in treating low anterior resection syndrome after rectal cancer surgery: Study protocol for a randomized controlled trial - Zi-Yue Wang; Guang-Xia Shi; Yu Wang; Wei Pei; Ying-Chi Yang; Jing-Wen Yang; Xiao-Ya Wei; Jin-Ying Jia; Jian-Feng Tu; Cun-Zhi Liu (PLoS ONE, 2025)
Purpose Low anterior resection syndrome (LARS), a frequent postoperative complication of rectal resection, has been shown to significantly impact patients’ quality of life. Electroacupuncture (EA), a non-pharmaceutical treatment, ameliorates gastrointestinal symptoms and promotes bowel movement. However, high-quality clinical evidence is lacking. This study aimed to determine whether EA can improve LARS symptoms compared with sham electroacupuncture (SA). Study design and methods This multicenter, randomized, sham-controlled clinical trial will be carried out across the outpatient clinics of three tertiary medical centers in China. A total of 136 patients with LARS who meet the inclusion criteria will be randomly allocated, in equal proportions (1:1), to either the EA or SA group. Each patient will undergo treatment three times weekly during the first four weeks and twice-weekly sessions over the subsequent four weeks. After the intervention, a 24-week follow-up period will be conducted. The primary outcome is the change in the LARS score from baseline to the end of week 8. Secondary outcomes include changes in the LARS score at other time points, response rate of patients showing reduced defecation dysfunction, subjective distress related to intestinal symptoms, Wexner Diarrhea score, Bristol Bowel Diary, EORTC-QLQ-C30 Quality of Life Questionnaire, and Fecal Incontinence Quality of Life Scale. Discussion This study will provide evidence of EA from multiple perspectives, investigate its potential application in LARS after rectal cancer surgery, and guide the development of therapy tailored to meet specific individual health needs. Ethics and dissemination Ethical approval for this study was granted by the Ethics Committee of Beijing University of Chinese Medicine (No. 2024BZYLL0402). All participants enrolled in the trial will provide written informed consent prior to randomization. Results will be prepared for submission to a peer-reviewed academic journal. Trial registration ITMCTR2024000195. International Traditional Medicine Clinical Trial Registry (http://itmctr.ccebtcm.org.cn/zh-CN/Home/ProjectView?pid=badb9af5-248b-4818-b3b6-25002f0fa0d5).